Elevational size variation and two new species of torrent frogs from Peninsular Malaysia (Anura: Ranidae: Amolops Cope) - Onn, Chan Kin; Abraham, Robin Kurian; Grismer, Jesse L.; Grismer, L. Lee (Zootaxa, 2018)
Previously, only one species of torrent frog (Amolops larutensis) was thought to occur throughout Peninsular Malaysia. However, genomic work has demonstrated that populations from eastern Peninsular Malaysia form two separate lineages that are genetically distinct from A. larutensis that is now restricted to the western half of Peninsular Malaysia. This study demonstrates that all three lineages can be morphologically distinguished from each other, thereby providing additional support for the recognition of the eastern lineages as two distinct species. These lineages are described herein as Amolops gerutu sp. nov. from the eastern states of Kelantan, Terengganu, and Pahang, and A. australis sp. nov. from the southern-most state of Johor. In general, these two new species form a clade that is sister to A. larutensis and can be readily distinguished from it by having: (1) considerably denser and more pronounced dorsal tubercles, and (2) the posterodorsal surface of thighs having dense, dark stippling as opposed to broad vermiculations. Although differences in other morphometric characters were detected, their utility as diagnostic characters should be applied with caution due to the large intraspecific variation that overlaps among different species in many of the characters we measured. As such, we advocate for the use of tuberculation and pattern of the posterodorsal portion of the thighs as primary diagnostic characters. These characters can readily distinguish A. larutensis from the two new species. To differentiate A. australis sp. nov. from A. gerutu sp. nov. and A. larutensis, body size can be a good diagnostic character as A. australis sp. nov. is significantly smaller in both males (mean = 31.04 ± 1.59 mm) and females (mean = 46.48 ± 3.2 mm). Additionally, we show a strong positive correlation between body size and elevation, with populations from montane forests (>900 m asl) being considerably larger than populations at lower elevations.